Tailored interventions by community pharmacists and general practitioners improve adherence to statins in a Spanish randomized controlled trial. (7th April 2019) - Oñatibia‐Astibia, Ainhoa; Malet‐Larrea, Amaia; Larrañaga, Belen; Gastelurrutia, Miguel Ángel; Calvo, Begoña; Ramírez, Dulce; Cantero, Ignacio; Garay, Ángel; Goyenechea, Estibaliz
Abstract: Objective: To evaluate the impact of health professionals' intervention on adherence to statins, the influence on total cholesterol levels, and lifestyle patterns in patients with hypercholesterolemia and analyze the differences according to the center of recruitment. Study Setting: Forty‐six community pharmacies and 50 primary care centers of Spain. Study Design: Randomized controlled trial design (n = 746). Patients were assigned into adherent (ADH) or nonadherent group depending on their initial adherence to statins. Nonadherent patients were randomly assigned to intervention (INT) or nonintervention (NOINT) group. Patients enrolled in the INT group received an intervention depending on the cause of nonadherence. Patients in the ADH and NOINT groups received usual care. Intention‐to‐treat (ITT) analysis was performed with multiple imputation to replace the missing data. Data Collection: Adherence, total cholesterol levels, and lifestyle behaviors. Findings: The odds of becoming adherent during the 6 months was higher in the INT group compared to the NOINT group (OR = 1, 49; 95% CI: 1.30‐1.76; P < 0.001), especially in the community pharmacy group (OR = 2.34; 95% CI: 1.81‐3.03; P < 0.001). Adherent patients showed lower values of total cholesterol compared with nonadherent patients at baseline (ADH: 200.3 mg/dL vs NOADH: 216.7 mg/dL; P < 0.001) and at the endpoint (ADH: 197.3 mg/dL vs NOADH: 212.2 mg/dL; P < 0.001). More patients enrolled in the INT group practices exercise at the end of the study (INT: +26.6 percent; P = 0.002), and a greater number of patients followed a diet to treat hypercholesterolemia (+30.2 percent; P < 0.001). Conclusions: The intervention performed by health professionals, especially by community pharmacists, improved adherence to statins by hypercholesterolemic patients, and this improvement in adherence was accompanied by a reduction in total cholesterol levels and a healthier lifestyle.